2000
DOI: 10.1136/emj.17.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of forearm fractures in children: a viable alternative?

Abstract: Objective-A pilot study to investigate whether ultrasonography can be reliably used to demonstrate uncomplicated greenstick and torus fractures in children. Method-Children between the ages of 2 and 14 years with a high clinical suspicion of a non-articular, undisplaced forearm fracture were included. Ultrasound imaging of the injury was performed by a consultant radiologist who gave an immediate report. Standard radiographs of the forearm were then obtained and the patient treated in the normal way. The radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 10 publications
2
62
0
3
Order By: Relevance
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported both the sensitivity and specificity of PoCUS, and LRs were calculated from these values when the authors did not include them in their manuscripts. Twenty-five studies 7,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][41][42][43][44] were included, ranging from 26 to 653 patients. Collectively, these studies included 2,982 patients and identified 1,200 fractures, with fracture prevalence ranging from 7% to 71% (aggregate prevalence of 40.2%).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Multiple studies show that ultrasound for fracture diagnosis has good accuracy when used by clinicians [12][13][14][15] as well as when used by radiologists. 16,17 In addition, ultrasound is well tolerated by children, even in areas of injury. 12,15 Emerging data suggest that ultrasound diagnosis of skull fractures in children is promising, 13,15,[17][18][19][20] and additional investigation of its utility is warranted.…”
mentioning
confidence: 99%